The Effect of Business Capital and Financial Inclusion on Financial Performance of MSMEs in Malang Culinary Sector - Azizah, Nur Rohmatul; Rahadjeng, Erna Retna; Nurjannah, Dewi (Universitas Muhammadiyah Malang, 2023)
The purpose of this study is to analyze business capital and financial inclusion on the financial performance of micro-enterprises. The analytical tool used in this study is multiple linear regression analysis using SPSS 25. The population of this study is the culinary sector micro-enterprises that are in the Karangploso District data 2022. The sample determination in this study used total sampling with a total sample of 109 micro-enterprises in the culinary sector. The results show that business capital and financial inclusion simultaneously have a positive and significant impact on the financial performance of micro-enterprises. Partially, business capital has a positive and significant effect on the financial performance of micro-enterprises and financial inclusion has a positive and significant effect on the financial performance of MSMEs.